Pengaruh Pemahaman Akuntansi, Komitmen Karyawan, dan Peran Internal Audit Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Pada OPD Kab. Gianyar - Dewa Ayu Fibriyani; Ni Nengah Seri Ekayani; I. B. Made Putra Manuaba (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
This research was conducted on 26 OPD in the Gianyar Regency Government area using non-probability sampling techniques and purposive sampling methods which aim to examine the effect of accounting understanding, employee commitment, and the role of internal audit on the quality of local government financial reports. Respondents used in this study were 95 people consisting of staff or employees of the finance department at each agency, agency, and inspectorate. The data from the questionnaire answers from the respondents were tested by multiple linear regression analysis, the results of the study showed that the variables of accounting understanding, employee commitment, and the role of internal audit had a positive and significant effect on the quality of local government financial reports in OPD Kab. Gianyar.